Literature support to the Third World Studies Program of the College of Arts and Sciences, University of the Philippines - Martin, Ramon R.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1981)
This paper is more than a bibliographic compilation of literature available in the Third World Studies Program Reading Room of the College of Arts and Sciences, University of the Philippines. This is not a mere checklist of materials with annotations. This work exceeds its avowed aim and provides the reader with enlightening information about the Third World.
The research method employed in this study was the normative type of descriptive research wherein the Third World Studies Program Reading Room was surveyed and its collection listed and annotated. The Dissertation Abstracts International from 1970 to 1980 was referred to for individual studies on Third World. Several catalogs and brochures were consulted to identify institutions and publications engaged in Third World studies. And a member of the Third World Studies Program (TWSP) was interviewed on Third World research.
This special problem consist of three parts: Part I orients the reader with various concepts categorizing the Third World. It offers answers to most intriguing questions like: "Why Third World?" "What research are they doing?" "What is Third World really after?" The reader will also find a topical reading list on "Problems of underdevelopment and alternatives to development in the Third World." This part includes the addresses and activities of foreign publications on Third World.Part II, Chapter III although an adaptation, supplies the history, objectives, and basic functions of the recently established TWSP at the University of the Philippines for background information. Chapters IV and V of this portion consist of notes on various activities and accomplishments of the TWSP as added information. Examples of this are the publication of literature and teaching materials on Third World, the organization of the TWSP Resource Collection; the production of slide shows, the sponsorship of lecture - discussions, the academic cooperation with different local and foreign institutions and publications, the pursuance of current projects, and others.
The main part, Part III, is a compilation of literature on Third World that has been undertaken to preserve and document the knowledge contained in various materials in the TWSP Resource Collection. This annotated bibliography of almost 950 entries hopes to facilitate the efforts of researchers to identify what materials are accessible to them. Through this volume researchers are alerted of the existence of works on Third World studies that are not available elsewhere. This annotated bibliography is classified into primary, secondary, and tertiary sources and then arranged alphabetically by author. The primary sources consist of books, articles from books, articles from serials, theses and dissertations, addresses, essays, and lectures, institute papers, research reports, conference papers and pamphlets. The secondary sources consist of bibliographies, survey reports and catalog while the tertiary sources consist of directories, yearbooks and annual reports. Each entry is provided with an index or item number at the right hand column opposite the author. These are the number referred to in the "Author-Main Entry-Editor Index" which has been provided to facilitate the location of specific work in the text.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Underdeveloped areas -- Literature; University of the Philippines Diliman. College of Arts and Sciences Third World Studies Program